Cost Effective Construction for Low Income Earners with MRTB and MFS - S.R.Swathi, S; Varuna Lakshmi, G; Muthu, D; Venkatasubramanian, C; Nagavalli, M (International Journal of Engineering and Technology, 2018)
India is a developing country having 14% (Pew Research Centre) population of low income group. The desire to own a house especially for low income and middle class families has become a virtual reality. Hence it is required to go in for an innovative, eco-friendly and cost efficient technology for raising of houses enabling the ordinary persons to build houses at owing to their financial status. The materials and techniques which are adopted have to be durable, economical and accepted by users. This study of low cost housing focuses mostly on personal satisfaction levels and the need of quality, particularly with regard to the place of abode. Hence, to provide the basic needs to the low income earners, this economical housing concept with minimum financial statement/investment has been suggested. The reduced construction cost through suitable management plans is obtained by appropriate use of locally available materials, labour and technology without compromising on the strength and life of the structure.Â In this study, it has been found that about 12% of total bricks and 22% of materials can be saved by using Modified Rat Trap Bond for walls and Modified Filler Slab for roofs respectively, which may be applied practically for government low cost dwellings. Â Â